Does metabolic water control the phosphate oxygen isotopes of microbial cells? - Weiner, Tal; Tamburini, Federica; Keren, Nir; Keinan, Jonathan; Angert, Alon (Frontiers in Microbiology, 2023)
The oxygen isotopes ratio (δ18O) of microbial cell water strongly controls the δ18O of cell phosphate and of other oxygen-carrying moieties. Recently it was suggested that the isotopic ratio in cell water is controlled by metabolic water, which is the water produced by cellular respiration. This potentially has important implications for paleoclimate reconstruction, and for measuring microbial carbon use efficiency with the 18O-water method. Carbon use efficiency strongly controls soil organic matter preservation. Here, we directly tested the effect of metabolic water on microbial cells, by conducting experiments with varying the δ18O of headspace O2 and the medium water, and by measuring the δ18O of cell phosphate. The latter is usually assumed to be in isotopic equilibrium with the cell’s water. Our results showed no correlation between the δ18O of O2 and that of the cell phosphate, contradicting the hypothesis that metabolic water is an important driver of δ18O of microbial cell water. However, our labeled 18O water experiments indicated that only 43% of the oxygen in the cell’s phosphate is derived from equilibration with the medium water, during late-log to early-stationary growing phase. This could be explained by the isotopic effects of intra-and extra-cellular hydrolysis of organic compounds containing phosphate.